1998
DOI: 10.1007/s004649900697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon dioxide pneumoperitoneum on bacteremia and severity of peritonitis in an experimental model

Abstract: In rats, pneumoperitoneum can't cause a more severe peritonitis but it does induce an increase in the rate of bacteremia within the early 6-h period of peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 5 publications
3
25
0
1
Order By: Relevance
“…It is likely, therefore, that the elevated intra-abdominal pressure used to maintain pneumoperitoneum may increase the plasma endotoxin level. In contrast, some experimental peritonitis studies have reported that positive pressure insufflation of the peritoneal cavity did not increase bacterial translocation from the peritoneal cavity into the bloodstream [15][16][17]. However, changes in plasma endotoxin levels immediately after the operative procedure were not measured in those studies.…”
Section: Discussionmentioning
confidence: 40%
“…It is likely, therefore, that the elevated intra-abdominal pressure used to maintain pneumoperitoneum may increase the plasma endotoxin level. In contrast, some experimental peritonitis studies have reported that positive pressure insufflation of the peritoneal cavity did not increase bacterial translocation from the peritoneal cavity into the bloodstream [15][16][17]. However, changes in plasma endotoxin levels immediately after the operative procedure were not measured in those studies.…”
Section: Discussionmentioning
confidence: 40%
“…Study in rats showed that pneumoperitoneum causes intestinal ischemia with oxygen free radical production and bacterial translocation, related to mechanical pressure of CO 2 17 . Other studies focused on whether a pneumoperitoneum amplifies the extent and severity of peritonitis or of bacteremia in various animal models 18,19,20,21 . Findings from these investigations are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It has not been clear whether a laparoscopic approach worsens the septic state or whether minimally invasive surgery is beneficial in these critically ill patients. Experimental model -Several animal models of peritoneal sepsis have been described varying in many respects, including the specific animal utilized and the method of sepsis 20,23,24,25 . The model of creating sepsis used in this study was adapted from the work of Hanly et al 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of pneumoperitoneum in infections remains a controversial issue. Sare et al 9 and Ipek et al 10 demonstrated in an experimental study that pneumoperitoneum induced greater bacteremia than the laparoscopic technique 9,10 . In contrast, Benoit et al 2 who conducted a prospective analysis of patients operated using the videolaparoscopic approach for acute appendicitis, with and without peritonitis, observed no positive blood cultures after performing the procedure, nor incidence of septic complications, and reported no increase in morbidity 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Colonies UFC/ml 4-Anti-sepsis using polyvinylpyrrolidone iodine; 5-A small incision was made into the abdominal wall to introduce an 18 abocath-type catheter which was affixed using polyglycolic acid 3-0 thread above the umbilical scar; 6-Inoculation with 2.0ml of a solution containing Escherichia coli ATCC at a concentration of 10 10 UFC and 1ml of barium sulfate; …”
Section: Animalmentioning
confidence: 99%